Empowering Character Through Culture: The Role of Teachers in Integrating Local Wisdom in Primary Education - Nurdin, Muhammad; Efendi AS, Arif; Kamil, Ahmad; Khaliq, Muh. Idham; Muliyadi, Muliyadi (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Character education based on local wisdom is a strategic approach to shaping students' personalities in alignment with regional cultural values. This study aims to explore the role of teachers in instilling character education through learning activities integrated with the local culture of Enrekang at MIS Muhammadiyah┬áKalosi. The research employed a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The findings reveal that teachers play a central role in fostering character values through modeling, habituation, and reinforcement of local cultural values such as mutual cooperation, tolerance, deliberation, and respect for parents and teachers. Teachers also face several challenges, including limited instructional time, lack of parental support, and students' low understanding of character values. To overcome these issues, teachers adopt adaptive strategies such as integrating character values into non-formal activities and enhancing communication with parents. These findings imply that the success of contextual character education requires sustained collaboration among schools, families, and the broader community.┬á┬á